Response of Bread Wheat Genotypes for Drought and Low Nitrogen Stress Tolerance - Sbongeleni Duma; Hussein Shimelis; Toi John Tsilo (Agronomy, 2022)
Drought stress and nitrogen (N) deficiency are the major causes of yield losses in bread wheat (Triticum aestivum) production. Breeding wheat cultivars with combined drought and low N stress tolerance is an economical approach for yield gains. The objective of this study was to evaluate the response of diverse bread wheat genotypes under drought and low N stress conditions to select high-performing genotypes for developing breeding populations and production to mitigate against drought and low N stress. Fifty bread wheat genotypes were evaluated under drought-stressed (DS) and non-stressed (NS) conditions and N application rates of 50, 100 and 200 kg N ha−1. The experiments were conducted in a controlled environment and field conditions during the 2019/20 cropping season. Data on grain yield and yield components were collected and subjected to statistical analysis. The four-way interaction involving genotype, water regime, N treatments and testing environment had a significant (p < 0.05) effect on all assessed agronomic traits, suggesting that genotype response depended on the treatment combinations. Drought stress and 50 kg N ha−1 reduced grain yield by 20% compared to NS and 50 kg N ha−1. The grain yield ranged from 120 to 337 g/m2, with a mean of 228 g/m2 under DS. Under DS and 200 kg N ha−1, the genotype designated as SBO 19 had a higher grain yield of 337 g/m2, followed by SBO 22 (335 g/m2), SBO 16 (335 g/m2), SBO 04 (335 g/m2) and SBO 33 (335 g/m2). Grain yields under DS and 50 kg N ha−1, and NS and 50 kg N ha−1 had a positive and significant correlation (r > 0.5; p < 0.01) with most of the evaluated traits. Highly correlated traits directly contribute to total yield gain and should be incorporated during the selection of high-yielding genotypes. The study identified the 10 best lines that are high-yielding with early flowering and maturity under DS or NS conditions and the three N treatments. The selected lines are recommended as breeding parents to develop drought-adapted and N-use efficient genetic resources. The identified genotypes are important for sustainable wheat production and effective breeding of improved cultivars to mitigate drought stress and soil nutrient deficiencies, to ensure food security in Sub-Saharan Africa.